2000
DOI: 10.1590/s0100-204x2000000200005
|View full text |Cite
|
Sign up to set email alerts
|

Intervalo de confiança "bootstrap" como ferramenta para classificar raças do nematóide de cisto da soja

Abstract: RESUMO -Estimativas bootstrap da média aritmética dos genótipos de soja Pickett, Peking, PI88788 e PI90763 e os intervalos de confiança obtidos pela teoria normal e através da distribuição bootstrap deste estimador, como o percentil bootstrap e o BCa, correção para o viés e aceleração, do parâmetro de diferenciação da cultivar padrão de suscetibilidade Lee são utilizados para classificar raças do nematóide de cisto da soja. Os intervalos de confiança obtidos a partir da distribuição bootstrap apresentaram meno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The ranges of the frequentist and bootstrap confidence intervals for downy mildew severity in soybean were similar. Other authors have also observed such similarities for the frequentist and bootstrap confidence intervals in simple random sampling (PEREIRA et al, 2000) and stratified sampling (CUSI, 2007).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 69%
“…The ranges of the frequentist and bootstrap confidence intervals for downy mildew severity in soybean were similar. Other authors have also observed such similarities for the frequentist and bootstrap confidence intervals in simple random sampling (PEREIRA et al, 2000) and stratified sampling (CUSI, 2007).…”
Section: Discussion and Concluding Remarksmentioning
confidence: 69%